Language, cultural and linguculturalology - Allanazarova, Nigora (Science and Education, 2023)
This article studies how culture is reflected in language and human society advances our understanding of various cultures and mentalities as well as intercultural communication. This study aims to trace the history of cultural linguistics’ emergence as a distinct scientific field, determine its origins, and assess its contemporary condition.